Heave and pullout studies of geogrid-encased granular pile-anchors in expansive clay beds. Issue 1 (4th February 2021) - Raghuram, Ammavajjala Sesha Sai; Phanikumar, B. R.; Purnanandam, K.; Rao, A. Srirama
Abstract : This paper presents the heave and pullout studies of plain granular pile-anchors (GPAs) and geogrid-encased granular pile-anchors. Experiments were conducted in CBR moulds and fabricated moulds of size 381 x 381 x 457 mm in expansive clays. GPA is an innovative technique developed for reducing heave and improving bearing capacity and pullout capacity. In this study, GPAs were encased in geogrids to augment the engineering performance of the system. Tests were conducted in CBR moulds and fabricated larger moulds to study and compare the heave and pullout behavior of the plain GPAs and the geogrid-encased GPAs. Results indicated that the clay beds reinforced with geogrid-encased GPAs showed better heave and pullout behaviour. Heave respectively decreased by 90.8% and 92.5% in the case of plain and geogrid-encased GPAs installed in the CBR moulds, and by 95.12 % and 98.3% in the case of plain and geogrid-encased GPAs installed in fabricated large moulds. Pullout load on geogrid-encased GPAs in CBR moulds improved by 42.17% over that on plain GPAs and pullout load on geogrid-encased GPAs in the fabricated large moulds improved by 52.25% over that on plain GPAs.